The Impact of Infaq and Shadaqah (ZIS) Zakat Funds Distribution and Utilization on Mustahic Consumption Behavior with Transparency as Intervening Variables (Case Study of Darul Mursyid Islamic Boarding School Bazis) - Juniar Siregar; Ibrahim Siregar; Darwis Harahap (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The poor utilization of zakat funds given to mustahik is the driving force behind this study. According to several observations made by researchers, some mustahik do not utilization the ZIS funds in accordance with their designation, either in operating or growing their business. In some cases, there are also some Mustahik who used the ZIS funds for personal needs without disclosing how they were used. The goal of this study was to determine the impact of transparency as an intervening variable on the distribution and utilization of zakat infaq and shadaqah (ZIS) money on mustahik consumption behavior. This study is quantitative in nature. 62 samples make up the research's sample. A closed questionnaire on mustahik BAZIS Darul Mursyid Islamic Boarding School is used as the data gathering tool. The inner model, outer model, and testing of the intermediary hypothesis are all used in data analysis. Based on the research findings, it is known that the study's variables can explain 88.8% of the variance, while the consuming behavior variable's R2 value is 0.836, or 83.6 percent, and 16.7% of the variance can be accounted for by other study factors. The study's findings show that there is no relationship between distribution and transparency, but there is a relationship between utilization and transparency, and there is a relationship between distribution and consumption behavior. However, there is no relationship between transparency and consumption behavior, and there is no relationship between distribution and utilization.